2011
DOI: 10.1021/bi201483g
|View full text |Cite
|
Sign up to set email alerts
|

Nondegradative Ubiquitination of Apoptosis Inducing Factor (AIF) by X-Linked Inhibitor of Apoptosis at a Residue Critical for AIF-Mediated Chromatin Degradation

Abstract: Apoptosis inducing factor (AIF) is a mediator of caspase-independent cell death that is also necessary for mitochondrial energy production. How these seemingly opposite cellular functions of AIF are controlled is poorly understood. X-linked inhibitor of apoptosis (XIAP) is an endogenous inhibitor of caspases that also regulates several caspase-independent signaling pathways. The RING domain of XIAP possesses E3 ubiquitin ligase activity, though the importance of this function to signal regulation remains incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…Binding and import of mitochondrial import factor CHCHD4 relies on AIF-CTC and may enable AIF-CTC architectures via protein interaction (Hangen et al, 2015). In contrast, cell death regulator heat-shock protein 70 (Hsp70) (Schmitt et al., 2003) and E3-ubiquitin ligase X-linked inhibitor of apoptosis protein (XIAP) (Lewis et al, 2011) target residues near AIF’s Cβ-clasp (K192, K194) and dimerization interface (K255), respectively, suggesting a requirement for the closed, monomeric architecture of oxidized AIF. The recent discovery of added mitochondrial binding partners of AIF (Lenhausen et al, 2016; Nakao et al, 2015) and a PARP-1-dependent AIF-associated nuclease (Wang et al., 2016) opens further opportunities for finding how the mechanism for architectural switching defined here regulates AIF’s mitochondrial and cell death functions in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Binding and import of mitochondrial import factor CHCHD4 relies on AIF-CTC and may enable AIF-CTC architectures via protein interaction (Hangen et al, 2015). In contrast, cell death regulator heat-shock protein 70 (Hsp70) (Schmitt et al., 2003) and E3-ubiquitin ligase X-linked inhibitor of apoptosis protein (XIAP) (Lewis et al, 2011) target residues near AIF’s Cβ-clasp (K192, K194) and dimerization interface (K255), respectively, suggesting a requirement for the closed, monomeric architecture of oxidized AIF. The recent discovery of added mitochondrial binding partners of AIF (Lenhausen et al, 2016; Nakao et al, 2015) and a PARP-1-dependent AIF-associated nuclease (Wang et al., 2016) opens further opportunities for finding how the mechanism for architectural switching defined here regulates AIF’s mitochondrial and cell death functions in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…A second possibility is that the death-inducing activity of AIF is blocked by up-regulation of inhibitory molecules. We have recently shown that through a ubiquitinationdependent mechanism, the pro-survival protein X-linked inhibitor of apoptosis (XIAP) is capable of preventing AIF-mediated DNA degradation (56). XIAP is also elevated in prostate cancer (35,57), raising the possibility that XIAP blocks AIF death induction and allows the mitochondrial functions of AIF to support cancer cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…All constructs were confirmed by sequencing (GENEWIZ). The pCW7-His-Myc-ubiquitin plasmids (WT, K6R, K11R, K27R, K29R, K48R, and K63R) have been described (43).…”
Section: Methodsmentioning
confidence: 99%
“…Cell Lysis and Immunoprecipitation-Cell lysates were prepared in radioimmune precipitation assay buffer, urea lysis buffer, or CHAPS buffer (43,44). All lysis buffers were supplemented with 1 mM PMSF and one Complete Mini protease inhibitor mixture tablet (Roche Applied Science) prior to use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation